Identification of morphological guilds in streams fish communities and their application in the estimation of biomass - Martin-Smith, K.M. (Malaysian Journal of Science (MJS), 1996)
Length/weight relationships were examined in a tropical freshwater fish community to facilitate biomass estimation. The relationships of body weight to standard length were determined for 21 species of freshwater fishes in Sabah, Malaysia (18 species of Cyprinidae, 1 species each of Anguillidae, Mastacembelidae and Bagridae). Multiple comparison of regression lines by analysis of covariance revealed two major functional groups within which species were indistinguishable. These groups were designated 'flattened' and 'heavy-bodied' . In addition there were two species with an 'eel-like' morphology. Common regression equations were generated for each group which allowed biomass to be estimated solely from length-frequency data, without the need for species identification. Biomass was estimated from species-specific regressions and from guild-specific regressions using data from surveys of four streams. The difference between these values was less than 5% for three streams with diverse fish communities. For a fourth stream with only four species biomass was significantly underestimated. When the length-frequency data were grouped in intervals the error of estimation increased as the interval size increased. Size data grouped into 2 or 3 mm intervals gave estimates of biomass indistinguishable from raw data. It is suggested that the use of morphological guilds is a valid tool for freshwater fish survey work in the old-world tropics.